PENGARUH PANDEMI COVID-19 SECARA PSIKOLOGIS, ETOS KERJA, OMZET TERHADAP PRODUKTIVITAS USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN SLEMAN YOGYAKARTA - Ary Subiyantoro, SE, MM; Susatyo Herlambang (Jurnal Solusi, 2021)
Abstract The purpose of this study was to determine the psychological effect of the Covid-19 pandemic, work ethic and turnover on the productivity of micro, small and medium enterprises in Sleman Regency, Yogyakarta. Data collection techniques through interviews with data collection instruments in the form of questionnaires. This study uses quantitative analysis techniques using validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination, significance test (t test and F test). The results of the study obtained the results of the regression equation Y = -0.164 + 0.355 X1 + 0.447 X2 + 0.253 X3, while from the F test results, the calculated f value is 61.355, above the standard Sig significance value of 0.000 or f table of 3.97, or the value of significant is less than 0.05, which means that the Covid-19 pandemic psychologically, work ethic and turnover affect the productivity of micro, small and medium enterprises in Sleman Regency, Yogyakarta. Keywords : Covid-19 Pandemic, Psychological, Work Ethic, Turnover, Productivity